Conceptual design support by a genetic algorithm based approach - Sit, Choon Fatt. (2010)
The highly competitive and rapidly changing global business environment requires companies to deliver new products with higher quality, lower cost and shorter time to the market. To develop a successful product, the early design stage plays an extremely important role. This project explores the feasibility of adapting genetic algorithms in design concept generation.